ChemInform Abstract: Flash Chemistry Using Trichlorovinyllithium: Switching the Reaction Pathways by High‐Resolution Reaction Time Control. Issue 34 (August 2015) - Nagaki, Aiichiro; Takahashi, Yusuke; Henseler, Andrea; Matsuo, Chika; Yoshida, Jun‐ichi
Abstract Different types of products are obtained from a single parent compound in a flow microreactor system by control of the residence times.